Effect of Comprehensive Cerebral Protection Program on Cerebral Oxygen Metabolism and Vascular Endothelial Function in Elderly Patients with Acute Cerebral Infarction - Meihong ZHOU; Zhaojun HUANG (Iranian Journal of Public Health, 2019)
Background: We aimed to explore the effect of comprehensive cerebral protection on cerebral oxygen metabolism and vascular endothelial function in elderly patients with acute cerebral infarction.